How Does Muslim Consumer Interest the Implementation of Islamic Consumption Behaviour during The Covid-19 Pandemic? - Asma' Munifatussa'idah; Sulaeman Sulaeman (Universitas Ahmad Dahlan, 2021)
Introduction: The implementation of the Islamic consumption behaviour is applying consumption actions or behaviors under Islamic principles. The application of Islamic consumption is influenced by the motivation and interest of a person to get satisfaction with goods/services. Purpose: This research paper aims to analyze the influence of Muslim Consumer Interest in halal goods/services on the implementation of Islamic Consumption Behavior. Methodology: The analytical method used quantitative analysis of primary data with non-probability sampling techniques. A total of 110 respondents were surveyed through an online questionnaire on the Muslim consumer in Semarang. The analysis model using a linear regression model. Findings: The results in this study showed the consumption of halal goods/services by Muslim Consumer Interest (CI) has a positive and significant influence toward the implementation of Islamic Consumption Behavior (ICB) in Semarang. The results of this study have implications for the government and regional policymakers, especially in Semarang, as evaluation materials and policies for campaigning the Islamic consumption behavior program. In addition, this study also contribute to the existing literature and add to the study of Islamic consumption theory based on a quantitative analysis approach. Paper Type: Research Article